Psalm-Shaped Prayerfulness : A Guide to the Christian Reception of the Psalms - Daly-Denton, Margaret (Book collections on Project MUSE., 2011)
A school of prayer from the foreword by Wilfred J. Harrington, OP. For people who treasure the Psalms and yet are often quite mystified by them, help is at hand. Weaving together her expertise in Scripture and liturgy, Margaret Daly-Denton accompanies the reader through a profitable and enjoyable learning experience. From the Psalter as a collection of ancient Israelite religious poetry to the New Testament portrayal of Jesus as pray-er of the Psalms, Daly-Denton guides readers through the centuries-long process of reinterpretation that is ongoing as psalms sung in worship shape the everyday prayerfulness of Christians. Throughout this book, suggestions for further reading and contemplation point the reader toward self-directed learning. Written in an accessible and friendly style, Psalm-Shaped Prayerfulness is intended for newcomers to biblical studies, people training for ministry, church musicians, members of parish liturgy teams, and anyone with an interest in the scriptural roots of Christian spirituality.